2022
DOI: 10.36227/techrxiv.20289210.v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Singer’s algebraic transfer for all ranks s in some degrees and the negation of the dimension results for the graded spaces F2 ⊗ AF2 [x1,...,xs] in degrees s+ 5

Abstract: <p>Let Ps:=F2[x1,x2,...,xs] be the graded polynomial algebra over the prime field of two elements,F2, insvariables x1,x2,...,xs, each of degree one. This algebra is considered as a graded moduleover the mod-2 Steenrod algebra, A.  The classical "hit problem", initiated by Frank Peterson[Abstracts Amer. Math. Soc. 833 (1987), 55-89], concerned with seeking a minimal set of A-module Ps. Equivalently, when F2 is an A-module concentrated in degree 0, one can write downexplicitly a monomial basis for theZ-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As applications, we establish the dimension result for the cohit F 2 -module Q ⊗6 in generic degree 5(2 s+4 −1)+n 1 .2 s+4 and examine Conjecture 1.1 for bidegrees (5, 5 + n s ) with s ≥ 0. Next, as a continuation of the previous works in [ Boa93,Sum15,Phu23b,Phu22a,Phu22b,Phu22c,Phu22d], we shall investigate Conjecture 1.1 in bidegree (m, m + n) for n = 12 and arbitrary m > 0. The cases of ranks m = 1, 2, 3 are relatively easy to compute (cf.…”
Section: Statement Of Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As applications, we establish the dimension result for the cohit F 2 -module Q ⊗6 in generic degree 5(2 s+4 −1)+n 1 .2 s+4 and examine Conjecture 1.1 for bidegrees (5, 5 + n s ) with s ≥ 0. Next, as a continuation of the previous works in [ Boa93,Sum15,Phu23b,Phu22a,Phu22b,Phu22c,Phu22d], we shall investigate Conjecture 1.1 in bidegree (m, m + n) for n = 12 and arbitrary m > 0. The cases of ranks m = 1, 2, 3 are relatively easy to compute (cf.…”
Section: Statement Of Resultsmentioning
confidence: 87%
“…Although Z is the minimal spike, ω(X) = (5, 0, 0, 4, 0) > ω(Z) = (3, 3, 1, 1, 1). The reader is referred to [Phu22c] for further information about a basis of Q ⊗5 37 .…”
Section: • Allowable and Non-allowable Monomial A Monomialmentioning
confidence: 99%
“…Despite the fact that Z is the minimal spike, it can be observed that ω(X) = (5, 0, 0, 4, 0) > ω(Z) = (3, 3, 1, 1, 1). For further details about a basis of Q ⊗5 37 , we refer the reader to [Phu22c].…”
Section: • Allowable and Non-allowable Monomial A Monomialmentioning
confidence: 99%